(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: Objectives. The paper highlights the importance of the kinetic recovery program used to regain post‐arthrodesis hand function in the interphalangeal joint. Also, during the paper we will present both the techniques used and the methods applied in order to reduce pain and recover the remaining functional. Keywords: hand, fracture, arthrodesis, recovery, gaming sistem